2019
DOI: 10.4103/jmu.jmu_35_19
|View full text |Cite
|
Sign up to set email alerts
|

Is thyroid imaging reporting and data system useful as an adult ultrasonographic malignancy risk stratification method in pediatric thyroid nodules?

Abstract: Background:Data on thyroid imaging reporting and data system (TI-RADS) generally belong to studies performed in adults. Therefore, we aimed to evaluate the performance and utility of TI-RADS in the pediatric group.Materials and Methods:From January 2015 to 2018, 108 nodules were evaluated in 1028 thyroid ultrasound examinations. Images were retrospectively evaluated by two radiologists with 3 and 7 years of pediatric radiology experience, according to TI-RADS classification. Morphological findings of the detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…However, the DTC prevalence and the time from irradiation to DTC onset are in agreement with those estimates by the ATA guidelines [2]. Second, the sample size and the number of DTCs were limited; however, this is the first study evaluating the role of US-RSSs in paediatric patients with a well-known history of irradiation exposure, and overall, the number of patients included in this study is in line with others evaluating non-irradiated patients [23,27,30]. Finally, only for 19 out of 52 patients was a histopathological confirmation available.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, the DTC prevalence and the time from irradiation to DTC onset are in agreement with those estimates by the ATA guidelines [2]. Second, the sample size and the number of DTCs were limited; however, this is the first study evaluating the role of US-RSSs in paediatric patients with a well-known history of irradiation exposure, and overall, the number of patients included in this study is in line with others evaluating non-irradiated patients [23,27,30]. Finally, only for 19 out of 52 patients was a histopathological confirmation available.…”
Section: Discussionsupporting
confidence: 84%
“…This discrepancy could be related to the higher prevalence of malignancy in the irradiated population and to the histopathology which is exclusively papillary thyroid cancer (PTC). Indeed, a large part of the studies considered in this meta-analysis [ 22 , 23 , 27 ] excluded patients with a history of radiation exposure and included patients with thyroid cancer other than PTC (10%) for which the US-RSSs are often not reliable enough [ 17 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polat et al analyzed the TI-RADS classification, and the results indicated its use is safe in children. However, the authors noted the small sample size and indicated that more research is needed on a larger group of children [ 39 ]. Regrettably, some other reports contradicted this conclusion and showed that the use of these guidelines in children carries a risk of missing cancer in up to 22% of pediatric patients [ 38 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the usefulness of different classification systems has not yet been clearly assessed in the population of children and adolescents. Single data are available in the literature regarding the utility of assessing thyroid nodules in pediatric patients using scales such as the ATA, TI-RADS, ACR-TIRADS and EU-TIRADS, especially after exclusion of the dimension criterion [ 31 , 32 , 33 ]. Both analyzed classifications performed well in predicting malignancy in our study group, as none of the PTCs were assessed as U3, U2 or U1 in BTA nor intermediate, low or very low suspicion in ATA.…”
Section: Discussionmentioning
confidence: 99%